Addressing asymmetry of the charge and strain in a two-dimensional fullerene peapod - Valeš, V; Verhagen, T; Vejpravová, J; Frank, O; Kalbáč, M (Nanoscale, 2016)
We prepared a two-dimensional C70 fullerene peapod by the sequential assembly of (12)C graphene, C70 fullerenes and (13)C graphene. The local changes in the strain and doping were correlated with local roughness revealing asymmetry in the strain and doping with respect to the top and bottom graphene layers of the peapod.